Production of F1 Papilionanthe hookeriana (Rchb.f.) Schltr. homozygous and heterozygous: Amplified fragment length polymorphism (AFLP) analysis of flower colors and self and cross-pollination ability between different flower colors - Tontiworachai, B.; Deewatthanawong, R.; Intasam, N.; Buamas, S.; Promvai, S.; Maneechote, N.; Montri, N. (My University, 2023)
Results showed that seed germination of Papilionanthe hookeriana (Rchb.f.) Schltr. was not significantly different between self-pollination treatments, while the percentage of selfpollination ability and seedling numbers were significantly different at 0.01 and 0.05 levels, respectively. Pink and purple flowers had the highest self-pollination ability at 100% and the highest numbers of seedlings (1,295) for self-pollination of pink flowers. Percentages of crosspollination ability, pod size and weight, and seed weight were not significantly different between treatments, while percentages of seed germination and seedling numbers were significantly different at the 0.01 level. The PixPu hybrid showed 100% seed germination, whereas the PixWh hybrid yielded the highest number of seedlings (403.2). Amplified fragment length polymorphism (AFLP) technique was used to study the genetic relations between various flower colors of P. hookeriana (Rchb.f.) Schltr. and the F1 hybrids of self- and cross-pollinated plants were classified into two clusters by UPGMA methods.
Keywords: AFLP; Breeding; DNA fingerprint; Papilionanthe hookeriana